Correction to: Assessment of the macroalgal genetic resources maintained in European germplasm banks - Laurie Carol Hofmann; Inka Bartsch; Hendrik Pehlke; Cicero Alves-Lima; Luís M. Barreto; Ricardo Bermejo; Susana Coelho; Olivier De Clerck; Bente Edvardsen; Svenja Heesch; Vladyslava Hostyeva; Lucie Jaugeon; et al. (Journal of Applied Phycology, 2026)

Assessment of the macroalgal genetic resources maintained in European germplasm banks - Laurie Carol Hofmann; Inka Bartsch; Hendrik Pehlke; Cicero Alves-Lima; Luís M. Barreto; Ricardo Bermejo; Susana Coelho; Olivier De Clerck; Bente Edvardsen; Svenja Heesch; Vladyslava Hostyeva; Lucie Jaugeon; et al. (Journal of Applied Phycology, 2026)
Germplasm banks are important for preserving genetic diversity, yet the availability and long-term maintenance of macroalgal strains in germplasm banks is currently limited in European collections. To support future food security, restoration efforts, and biotechnological innovation, a strategy was recently developed for the long-term preservation of macroalgal genetic diversity. A foundational step in this effort is to assess the existing biodiversity, biogeographical distribution, and commercial relevance of seaweed cultures maintained in European collections. Using a universal data-collection template distributed widely across European seaweed networks, we compiled and analysed information on these seaweed cultures. As of November 2025, the resulting SeaStrains Database of European Seaweed Collections contains 2541 cultures representing 426 species, accounting for only 4% of global and 15% of European macroalgal diversity. The dataset reveals strong taxonomic bias: 74% are brown seaweeds (Ochrophyta), dominated by Laminaria , Saccharina , and Ectocarpus . Saccharina latissima is the most preserved species due to its scientific and commercial importance. Red and green algae are markedly underrepresented (11% and 14%, respectively), likely reflecting cultivation challenges and life-cycle knowledge gaps. Biogeographically, most cultures originate from cold- to warm-temperate zones, with limited representation of the South Atlantic, Indian Ocean, polar and remote regions. Over 60% of cultures are maintained at two institutions: the Culture Collection of Algae and Protozoa (Scotland) and the Alfred Wegener Institute (Germany). This work provides transparent, accessible information on Europe’s macroalgal germplasm resources and represents a crucial step toward a more robust and sustainable European seaweed sector aligned with UN SDG Target 2.5.

Nutritional response of a coccolithophore to changing pH and temperature - Roberta Johnson; Gerald Langer; Sergio Rossi; Ian Probert; Marta Mammone; Patrizia Ziveri (Limnology and Oceanography, 2022)
Coccolithophores are a calcifying unicellular phytoplankton group that are at the base of the marine food web, and their lipid content provides a source of energy to consumers. Coccolithophores are vulnerable to ocean acidification and warming, therefore it is critical to establish the effects of climate change on these significant marine primary producers, and determine potential consequences that these changes can have on their consumers. Here, we quantified the impact of changes in pH and temperature on the nutritional condition (lipid content, particulate organic carbon/nitrogen), growth rate, and morphology of the most abundant living coccolithophore species, Emiliania huxleyi . We used a regression type approach with nine pH levels (ranging from 7.66 to 8.44) and two temperatures (15°C and 20°C). Lipid production was greater under reduced pH, and growth rates were distinctly lower at 15°C than at 20°C. The production potential of lipids, which estimates the availability of lipids to consumers, increased under 20°C, but decreased under low pH. The results indicate that, while consumers will benefit energetically under ocean warming, this benefit will be mitigated by ocean acidification. The carbon to nitrogen ratio was higher at 20°C and low pH, indicating that the nutritional quality of coccolithophores for consumers will decline under climate change. The impact of low pH on the structural integrity of the coccosphere may also mean that coccolithophores are easier to digest for consumers. Many responses suggest cellular stress, indicating that increases in temperature and reductions in pH may have a negative impact on the ecophysiology of coccolithophores.

Plankton Planet: A frugal, cooperative measure of aquatic life at the planetary scale - Colomban de Vargas; Noan Le Bescot; Thibaut Pollina; Nicolas Henry; Sarah Romac; Sébastien Colin; Nils Haëntjens; Margaux Carmichael; Calixte Berger; David Le Guen; Johan Decelle; Frédéric Mahé; et al. (Frontiers in Marine Science, 2022)
In every liter of seawater there are between 10 and 100 billion life forms, mostly invisible, called marine plankton or marine microbiome, which form the largest and most dynamic ecosystem on our planet, at the heart of global ecological and economic processes. While physical and chemical parameters of planktonic ecosystems are fairly well measured and modeled at the planetary scale, biological data are still scarce due to the extreme cost and relative inflexibility of the classical vessels and instruments used to explore marine biodiversity. Here we introduce ‘Plankton Planet’, an initiative whose goal is to engage the curiosity and creativity of researchers, makers, and mariners to ( i ) co-develop a new generation of cost-effective (frugal) universal scientific instrumentation to measure the genetic and morphological diversity of marine microbiomes in context, ( ii ) organize their systematic deployment through coastal or open ocean communities of sea-users/farers, to generate uniform plankton data across global and long-term spatio-temporal scales, and ( iii ) setup tools to flow the data without embargo into public and explorable databases. As proof-of-concept, we show how 20 crews of sailors were able to sample plankton biomass from the world surface ocean in a single year, generating the first seatizen-based, planetary dataset of marine plankton biodiversity based on DNA barcodes. The quality of this dataset is comparable to that generated by Tara Oceans and is not biased by the multiplication of samplers. The data unveil significant genetic novelty and can be used to explore the taxonomic and ecological diversity of plankton at both regional and global scales. This pilot project paves the way for construction of a miniaturized, modular, evolvable, affordable and open-source citizen field-platform that will allow systematic assessment of the eco/morpho/genetic variation of aquatic ecosystems and microbiomes across the dimensions of the Earth system.

Analysis of the genomic basis of functional diversity in dinoflagellates using a transcriptome‐based sequence similarity network - Arnaud Meng; Erwan Corre; Ian Probert; Andres Gutierrez‐Rodriguez; Raffaele Siano; Anita Annamale; Adriana Alberti; Corinne Da Silva; Patrick Wincker; Stéphane Le Crom; Fabrice Not; Lucie Bittner (Molecular Ecology, 2018)
Dinoflagellates are one of the most abundant and functionally diverse groups of eukaryotes. Despite an overall scarcity of genomic information for dinoflagellates, constantly emerging high‐throughput sequencing resources can be used to characterize and compare these organisms. We assembled de novo and processed 46 dinoflagellate transcriptomes and used a sequence similarity network (SSN) to compare the underlying genomic basis of functional features within the group. This approach constitutes the most comprehensive picture to date of the genomic potential of dinoflagellates. A core‐predicted proteome composed of 252 connected components (CCs) of putative conserved protein domains (pCDs) was identified. Of these, 206 were novel and 16 lacked any functional annotation in public databases. Integration of functional information in our network analyses allowed investigation of pCDs specifically associated with functional traits. With respect to toxicity, sequences homologous to those of proteins found in species with toxicity potential (e.g., sxtA4 and sxtG ) were not specific to known toxin‐producing species. Although not fully specific to symbiosis, the most represented functions associated with proteins involved in the symbiotic trait were related to membrane processes and ion transport. Overall, our SSN approach led to identification of 45,207 and 90,794 specific and constitutive pCDs of, respectively, the toxic and symbiotic species represented in our analyses. Of these, 56% and 57%, respectively (i.e., 25,393 and 52,193 pCDs), completely lacked annotation in public databases. This stresses the extent of our lack of knowledge, while emphasizing the potential of SSNs to identify candidate pCDs for further functional genomic characterization.

Fighting hospital infection with new antibiotic molecules derived from microalgae: the NoMorFilm EU project - Amaral Raquel; Martins Clara; Assunção Mariana; Santos Lília; Soto Sara; Lombó Felipe; Römling Ute; Tredici Mario; Ortiz Fernando; Jensen Henrik; Foster Timothy; Rodolfi Liliana; et al. (Frontiers in Marine Science, 2016)

Marine protist diversity in E uropean coastal waters and sediments as revealed by high‐throughput sequencing - Ramon Massana; Angélique Gobet; Stéphane Audic; David Bass; Lucie Bittner; Christophe Boutte; Aurélie Chambouvet; Richard Christen; Jean‐Michel Claverie; Johan Decelle; John R. Dolan; Micah Dunthorn; et al. (Environmental Microbiology, 2015)
Summary Although protists are critical components of marine ecosystems, they are still poorly characterized. Here we analysed the taxonomic diversity of planktonic and benthic protist communities collected in six distant E uropean coastal sites. Environmental deoxyribonucleic acid ( DNA ) and ribonucleic acid ( RNA ) from three size fractions (pico‐, nano‐ and micro/mesoplankton), as well as from dissolved DNA and surface sediments were used as templates for tag pyrosequencing of the V4 region of the 18S ribosomal DNA. Beta‐diversity analyses split the protist community structure into three main clusters: picoplankton‐nanoplankton‐dissolved DNA , micro/mesoplankton and sediments. Within each cluster, protist communities from the same site and time clustered together, while communities from the same site but different seasons were unrelated. Both DNA and RNA ‐based surveys provided similar relative abundances for most class‐level taxonomic groups. Yet, particular groups were overrepresented in one of the two templates, such as marine alveolates ( MALV )‐ I and MALV‐II that were much more abundant in DNA surveys. Overall, the groups displaying the highest relative contribution were Dinophyceae, Diatomea, Ciliophora and Acantharia. Also, well represented were Mamiellophyceae, Cryptomonadales, marine alveolates and marine stramenopiles in the picoplankton, and Monadofilosa and basal F ungi in sediments. Our extensive and systematic sequencing of geographically separated sites provides the most comprehensive molecular description of coastal marine protist diversity to date.

Erratum to: On the description of Tisochrysis lutea gen. nov. sp. nov. and Isochrysis nuda sp. nov. in the Isochrysidales, and the transfer of Dicrateria to the Prymnesiales (Haptophyta) - El Mahdi Bendif; Ian Probert; Declan C. Schroeder; Colomban de Vargas (Journal of Applied Phycology, 2014)

On the description of Tisochrysis lutea gen. nov. sp. nov. and Isochrysis nuda sp. nov. in the Isochrysidales, and the transfer of Dicrateria to the Prymnesiales (Haptophyta) - El Mahdi Bendif; Ian Probert; Declan C. Schroeder; Colomban de Vargas (Journal of Applied Phycology, 2013)

Diversity patterns of uncultured Haptophytes unravelled by pyrosequencing in Naples Bay - Lucie Bittner; Angélique Gobet; Stéphane Audic; Sarah Romac; Elianne S. Egge; Sébastien Santini; Hiroyuki Ogata; Ian Probert; Bente Edvardsen; Colomban de Vargas (Molecular Ecology, 2013)
Haptophytes are a key phylum of marine protists, including ~300 described morphospecies and 80 morphogenera. We used 454 pyrosequencing on large subunit ribosomal DNA (LSU rDNA ) fragments to assess the diversity from size‐fractioned plankton samples collected in the Bay of Naples. One group‐specific primer set targeting the LSU rDNA D1/D2 region was designed to amplify Haptophyte sequences from nucleic acid extracts (total DNA or RNA) of two size fractions (0.8–3 or 3–20 μm) and two sampling depths [subsurface, at 1 m, or deep chlorophyll maximum (DCM) at 23 m]. 454 reads were identified using a database covering the entire Haptophyta diversity currently sequenced. Our data set revealed several hundreds of Haptophyte clusters. However, most of these clusters could not be linked to taxonomically known sequences: considering OTUs 97% (clusters build at a sequence identity level of 97%) on our global data set, less than 1% of the reads clustered with sequences from cultures, and less than 12% clustered with reference sequences obtained previously from cloning and Sanger sequencing of environmental samples. Thus, we highlighted a large uncharacterized environmental genetic diversity, which clearly shows that currently cultivated species poorly reflect the actual diversity present in the natural environment. Haptophyte community appeared to be significantly structured according to the depth. The highest diversity and evenness were obtained in samples from the DCM, and samples from the large size fraction (3–20 μm) taken at the DCM shared a lower proportion of common OTUs 97% with the other samples. Reads from the species Chrysoculter romboideus were notably found at the DCM, while they could be detected at the subsurface. The highest proportion of totally unknown OTUs 97% was collected at the DCM in the smallest size fraction (0.8–3 μm). Overall, this study emphasized several technical and theoretical barriers inherent to the exploration of the large and largely unknown diversity of unicellular eukaryotes.

Multiple microalgal partners in symbiosis with the acantharian Acanthochiasma sp. (Radiolaria) - Johan Decelle; Raffaele Siano; Ian Probert; Camille Poirier; Fabrice Not (Symbiosis, 2012)

In situ survey of life cycle phases of the coccolithophore Emiliania huxleyi ( Haptophyta ) - Miguel J. Frada; Kay D. Bidle; Ian Probert; Colomban de Vargas (Environmental Microbiology, 2012)
Summary The cosmopolitan coccolithophore Emiliania huxleyi is characterized by a strongly differentiated haplodiplontic life cycle consisting of a diploid phase, generally bearing coccoliths (calcified) but that can be also non‐calcified, and a non‐calcified biflagellated haploid phase. Given most studies have focused on the bloom‐producing calcified phase, there is little‐to‐no information about non‐calcified cells in nature. Using field mesocoms as experimental platforms, we quantitatively surveyed calcified and non‐calcified cells using the combined calcareous detection fluorescent in situ hybridization (COD‐FISH) method and qualitatively screened for haploid specific transcripts using reverse transcription‐PCR during E. huxleyi bloom successions. Diploid, calcified cells formed dense blooms that were followed by the massive proliferation of E. huxleyi viruses ( Eh Vs), which caused bloom demise. Non‐calcified cells were also detected throughout the experiment, accounting for a minor fraction of the population but becoming progressively more abundant during mid‐late bloom periods concomitant with Eh V burst. Non‐calcified cell growth also paralleled a distinct window of haploid‐specific transcripts and the appearance of autotrophic flagellates morphologically similar to haploid cells, both of which are suggestive of meiosis and sexual life cycling during natural blooms of this prominent marine phytoplankton species.